Ethnopharmacological Potential of Aspilia africana for the Treatment of Inflammatory Diseases. (19th June 2020) - Okello, Denis; Lee, Jun; Kang, Youngmin
Abstract : Inflammatory diseases are major health concerns affecting millions of people worldwide. Aspilia africana has been used for centuries by many African communities in the treatment of a wide range of health conditions, including inflammatory diseases, osteoporosis, rheumatic pains, and wounds. Analysis of the phytochemical composition of A . africana indicated that the plant is rich in a broad range of secondary metabolites, including flavonoids, alkaloids, tannins, saponins, terpenoids, sterols, phenolic compounds, and glycosides. This explains the efficacy of the plant in treating inflammation-related diseases, as well as several other health conditions affecting different African communities. The mechanisms of action of the anti-inflammatory phytochemical compounds in A . africana include inhibition of a number of physiological processes involved in the inflammatory process and synthesis or action of proinflammatory enzymes. The phytochemicals enhance anti-inflammatory biological responses such as inhibition of a number of chemical mediators including histamine, prostanoids and kinins, 5-lipoxygenase. and cyclooxygenase and activation of phosphodiesterase and transcriptase. Currently used anti-inflammatory medications are associated with several disadvantages such as drug toxicity and iatrogenic reactions, thereby complicating the treatment process. The adverse effects related to the use of these conventional synthetic drugs have been the driving force behind consideration of natural remedies, and efforts are being made toward the development of anti-inflammatory agents based on natural extracts. A . africana is rich in secondary metabolites, and its use as a traditional medicine for treating inflammatory diseases has been validated through in vitro and in vivo studies. Therefore, the plant could be further explored for potential development of novel anti-inflammatory therapeutics.